Canonical form of any expression (SOP/ POS) is the form where every minterm/ maxterm contains all the fundamental inputs.
We can convert any SOP/ POS expression to its canonical form by following method:
SOP Expression to Canonical SOP Expression:
To convert SOP to canonical SOP expression, let us understand by taking an example .
Let, F(A, B, C) = A'B + AB'C
ANDing 1 to the minterm with missing input,
A'B + AB'C = A'B.1 + AB'C (property of 1)
= A'B.(C+C') + AB'C (complementarity law)
= A'BC + A'BC' + AB'C (distributive law)
now,
F(A, B, C) = A'BC + A'BC' + AB'C
hence converted to Canonical Form.
POS Expression to Canonical POS Expression:
To convert POS to canonical POS expression, let us understand by taking an example .
Let, F(A, B, C) = (A+B').(A+B'+C)
ORing 0 to the maxterm with missing input,
(A+B').(A+B'+C) = (A+B'+0).(A+B'+C) (property of 0)
= (A+B'+C.C').(A+B'+C) (complementarity law)
= (A+B'+C).(A+B'+C').(A+B'+C) (distributive law)
= (A+B'+C).(A+B'+C).(A+B'+C') (commutative law)
= (A+B'+C).(A+B'+C') (idempotence law)
now,
F(A, B, C) = (A+B'+C).(A+B'+C')
hence converted to Canonical Form.
No comments:
Post a Comment